Void-shape effects on strength properties of nanoporous materials. (December 2017) - Brach, Stella; Cherubini, Stefano; Kondo, Djimédo; Vairo, Giuseppe
Highlights: Strength properties of spheroidal-nanovoided single-crystal samples are numerically investigated. Prolate, oblate and spherical void shapes are considered. Several mechanical loadings, including axisymmetric and shear strain-rate states are applied. Void-shape effects induce a weakening of the computational sample as the void aspect-ratio is varied. Strength measures highly depend on the hydrostatic, second- and third-order deviatoric stress invariants. Abstract: In this paper, strength properties of nanoporous materials with spheroidal nanocavities are investigated via a Molecular Dynamics approach applied to a nanovoided aluminium single crystal, in the case of a fixed porosity level, and for prolate, oblate and spherical void shapes. Estimates of the effective strength domain are provided, by considering several mechanical loadings including axisymmetric and shear strain-rate states. Void-shape effects are quantified for different values of the void aspect ratio, mainly resulting in an overall weakening of the sample as the spheroidal nanovoid assumes either an oblate or a prolate shape, in comparison to the case of a spherical void. Finally, it is observed that the computed strength profiles exhibit the following specific features: (i) a strong dependence on the hydrostatic, second-order and third-order deviatoric stress invariants, (ii) more significant void-shape effects for triaxial-expansion stress states with a small hydrostatic component, and (iii) a more pronounced influence of the spheroid shape, as the aspect ratio is varied, in the presence of an oblate nanovoid rather than of a prolate one.